What Is the Current Knowledge About Sublay/Retro-Rectus Repair of Incisional Hernias? - Köckerling, Ferdinand; Schug-Pass, Christine; Scheuerlein, Hubert (Frontiers in Surgery, 2018)
Introduction There continues to be very little agreement among experts on the precise treatment strategy for incisional hernias. That is the conclusion drawn from the very limited scientific evidence available on the repair of incisional hernias. The present review now aims to critically assess the data available on the sublay / retro-rectus technique for repair of incisional hernia. Material and Methods A systematic search of the literature was performed in May 2018 using Medline, PubMed, and the Cochrane Library. This article is based on 77 publications. Results The number of available RCTs that permit evaluation of the role of the sublay / retro-rectus technique in the repair of only incisional hernia is very small. The existing data suggest that the sublay / retro-rectus technique has disadvantages compared with the laparoscopic IPOM technique for repair of incisional hernia, but in that respect has advantages over all other open techniques. However, the few existing studies provide only a limited level of evidence for assessment purposes. Conclusion Further RCTs based on a standardized technique are urgently needed for evaluation of the role of the sublay / retro-rectus incisional hernia repair technique.